Respuesta :

Answer:

[tex]p(x) = (x-4)(x - \frac{5}{3})(x - 1)[/tex]

Step-by-step explanation:

Solving a quadratic equation:

Given a second order polynomial expressed by the following equation:

[tex]ax^{2} + bx + c, a\neq0[/tex].

This polynomial has roots [tex]x_{1}, x_{2}[/tex] such that [tex]ax^{2} + bx + c = a(x - x_{1})*(x - x_{2})[/tex], given by the following formulas:

[tex]x_{1} = \frac{-b + \sqrt{\bigtriangleup}}{2*a}[/tex]

[tex]x_{2} = \frac{-b - \sqrt{\bigtriangleup}}{2*a}[/tex]

[tex]\bigtriangleup = b^{2} - 4ac[/tex]

In this question:

We have the polynomial [tex]p(x) = 3x^3-20x^2+37x-20[/tex]

It has a known factor [tex]x - 4[/tex]. This means that the polynomial can be written as:

[tex]p(x) = (x-4)q(x)[/tex]

In which q(x) is a second order polynomial, because p is of the third degree and q is of the first degree(3 - 1 = 2). So

[tex]q(x) = ax^2 + bx + c[/tex]

We have to find a, b and c. Then

[tex]3x^3-20x^2+37x-20 = (x-4)(ax^2 + bx + c)[/tex]

[tex]3x^3-20x^2+37x-20 = = ax^3 + (-4a + b)x^2 + (c - 4b)x - 4c[/tex]

Comparing both sides, we have that

[tex]a = 3[/tex]

[tex]-4c = -20 \rightarrow c = 5[/tex]

[tex]c - 4b = 37[/tex]

[tex]-4b = 32 \rightarrow b = -8[/tex]

Now we find the roots of this polynomial.

[tex]\bigtriangleup = b^{2} - 4ac = (-8)^2 - 4(3)(5) = 64 - 60 = 4[/tex]

[tex]x_{1} = \frac{-(-8) + \sqrt{4}}{2*3} = \frac{5}{3}[/tex]

[tex]x_{2} = \frac{-(-8) - \sqrt{4}}{2*3} = 1[/tex]

So, as a product of it's factors, we have that q is:

[tex]q(x) = (x - \frac{5}{3})(x - 1)[/tex]

And p(x)

[tex]p(x) = (x-4)q(x)[/tex]

[tex]p(x) = (x-4)(x - \frac{5}{3})(x - 1)[/tex]

Answer: (x-4)(3x-5)(x-1)

Step-by-step explanation:

ACCESS MORE